ICONOLOGY-ICONOGRAPHY OF ISLAMIC ARTS BY TITA RUBIES AND RISPULES AT THE EXHIBITION OF FRAGMENTS OF MODERN INDONESIAN ART AT OHD MUSEUM: IKONOLOGI-IKONOGRAFI SENI RUPA ISLAM KARYA TITA RUBI DAN RISPUL PADA PAMERAN FRAGMENTS OF MODERN INDONESIAN ART DI OHD MUSEUM - Khairi, Khairi (UNIVERSITAS NUSA PUTRA, 2024)
ABSTRACT Islamic art, as a manifestation of culture, presents its distinctive style and carries the spirit of its time through its iconography and iconology, which not only serve as therapeutic media for religious buildings but also for works of painting. This study further elaborates on the iconology and iconography of contemporary Islamic art today through the works of Tita Rubi and Rispul in the